Results 1 to 2 of 2
Like Tree2Thanks
  • 2 Post By Prove It

Math Help - Trig. equation

  1. #1
    Member
    Joined
    Dec 2010
    Posts
    82
    Thanks
    2

    Trig. equation

    No. of solution of the equation \cos \left(15\theta \right) = \cos \left(3\theta \right) ,where \theta \in \left[0,2\pi\right]
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor
    Prove It's Avatar
    Joined
    Aug 2008
    Posts
    11,518
    Thanks
    1404

    Re: Trig. equation

    Using the identity $\displaystyle \begin{align*} \cos{(X)} = \frac{e^{i\,X} + e^{-i\,X}}{2} \end{align*}$ we have

    $\displaystyle \begin{align*} \cos{(15x )} &= \cos{(3x )} \\ \frac{e^{15i\,x} + e^{-15i\,x}}{2} &= \frac{e^{3i\,x} + e^{-3i\,x}}{2} \\ e^{15i\,x} + e^{-15i\,x} &= e^{3i\,x} + e^{-3i\,x} \\ e^{3i\,x} \left( e^{15i\,x} + e^{-15i\,x} \right) &= e^{3i\,x} \left( e^{3i\,x} + e^{-3i\,x} \right) \\ e^{18i\,x} + e^{-12i\,x} &= e^{6i\,x} + 1 \\ e^{12i\,x} \left( e^{18i\,x} + e^{-12i\,x} \right) &= e^{12i\,x} \left( e^{6i\,x} + 1 \right) \\ e^{30i\,x} + 1 &= e^{18i\,x} + e^{12i\,x} \\ e^{30i\,x} - e^{18i\,x} - e^{12i\,x} + 1 &= 0 \\ \left( e^{6i\,x} \right) ^5 - \left( e^{6i\,x} \right) ^3 - \left( e^{6i\,x } \right) ^2 + 1 &= 0 \\ u^5 - u^3 - u^2 + 1 &= 0 \textrm{ if we let } u = e^{6i\,x} \end{align*}$

    $\displaystyle \begin{align*} u = 1 \end{align*}$ is an obvious solution, so $\displaystyle \begin{align*} (u - 1) \end{align*}$ is a factor. Long dividing gives

    $\displaystyle \begin{align*} \left( u - 1 \right) \left( u^4 + u^3 - u - 1 \right) &= 0 \end{align*}$

    $\displaystyle \begin{align*} ( u - 1) \end{align*}$ is another obvious factor, so long dividing again gives

    $\displaystyle \begin{align*} \left( u - 1 \right) ^2 \left( u^3 + 2u^2 + 2u + 1 \right) &= 0 \end{align*}$

    $\displaystyle \begin{align*} u = -1 \end{align*}$ is another solution, which means $\displaystyle \begin{align*} (u + 1) \end{align*}$ is a factor. Long dividing again gives

    $\displaystyle \begin{align*} \left( u - 1 \right) ^2 \left( u + 1 \right) \left( u^2 + u + 1 \right) &= 0 \\ u = 1\textrm{ or } u = -1 \textrm{ or } u &= \frac{-1 \pm \sqrt{1^2 - 4 \cdot 1 \cdot 1}}{2 \cdot 1} \\ u = 1 \textrm{ or } u = -1 \textrm{ or } u = -\frac{1}{2} - \frac{\sqrt{3}}{2}i \textrm{ or } u &= -\frac{1}{2} + \frac{\sqrt{3}}{2}i \\ u = e^{2k\, \pi \, i } \textrm{ or } u = e^{(2k + 1 ) \, \pi \, i } \textrm{ or } u = e^{\frac{2\pi}{3}k\, i } \textrm{ or } u &= e^{-\frac{\pi}{3}k\,i} \end{align*}$

    Note that k is an integer.

    Case 1:

    $\displaystyle \begin{align*} u &= e^{2k\,\pi\,i} \\ e^{6i\,x} &= e^{2k\,\pi\,i} \\ 6i\,x &= 2k\,\pi \, i \\ x &= \frac{\pi}{3}k \\ x &= \left\{ 0, \frac{\pi}{3}, \frac{2\pi}{3}, \pi, \frac{4\pi}{3}, \frac{5\pi}{3}, 2\pi \right\} \textrm{ if } x \in [0, 2\pi] \end{align*}$

    Case 2:

    $\displaystyle \begin{align*} u &= e^{(2k+1)\,\pi\,i} \\ e^{6i\,x} &= e^{(2k+1)\,\pi\,i} \\ 6i\,x &= (2k+1)\,\pi\,i \\ x &= \left( \frac{ \pi}{6} \right) \left( 2k + 1 \right) \\ x &= \left\{ \frac{\pi}{6}, \frac{\pi}{2}, \frac{5\pi}{6}, \frac{7\pi}{6}, \frac{3\pi}{2} , \frac{11\pi}{6} \right\} \textrm{ if } x \in [0, 2\pi] \end{align*}$

    Case 3:

    $\displaystyle \begin{align*} u &= e^{\frac{2\pi}{3}\,k\,i} \\ e^{6i\,x} &= e^{\frac{2\pi}{3}\,k\,i} \\ 6i\,x &= \frac{2\pi}{3}\,k\,i \\ x &= \frac{\pi}{9}\,k \\ x &= \left\{ 0, \frac{\pi}{9}, \frac{2\pi}{9}, \frac{\pi}{3}, \frac{4\pi}{9} , \frac{5\pi}{9} , \frac{2\pi}{3}, \frac{7\pi}{9} , \frac{8\pi}{9} , \pi , \frac{10\pi}{9} , \frac{11\pi}{9} , \frac{4\pi}{3} , \frac{13\pi}{9} , \frac{14\pi}{9} , \frac{5\pi}{3}, \frac{16\pi}{9}, \frac{17\pi}{9} , 2\pi \right\} \textrm{ if } x \in [0, 2\pi]\end{align*}$

    Case 4:

    $\displaystyle \begin{align*} u &= e^{-\frac{\pi}{3}\,k\,i} \\ e^{6i\,x} &= e^{-\frac{\pi}{3}\,k\,i} \\ 6i\,x &= -\frac{\pi}{3}\,k\,i \\ x &= - \frac{\pi}{18}k \\ x &= \left\{ 0 , \frac{\pi}{18}, \frac{\pi}{9} , \frac{3\pi}{18}, \frac{2\pi}{9}, \frac{5\pi}{18}, \frac{\pi}{3}, \frac{7\pi}{18}, \frac{4\pi}{9}, \frac{\pi}{2}, \frac{5\pi}{9}, \frac{11\pi}{18}, \frac{2\pi}{3}, \frac{13\pi}{18}, \frac{7\pi}{9}, \frac{5\pi}{6}, \frac{8\pi}{9}, \frac{17\pi}{18} , \pi, \frac{19\pi}{18}, \frac{10\pi}{9}, \frac{7\pi}{6}, \frac{11\pi}{9}, \frac{23\pi}{18}, \frac{4\pi}{3}, \frac{25\pi}{18} , \frac{13\pi}{9} , \frac{3\pi}{2}, \frac{14\pi}{9} , \frac{29\pi}{18} , \frac{5\pi}{3}, \frac{31\pi}{18}, \frac{16\pi}{9}, \frac{11\pi}{6} , \frac{17\pi}{9}, \frac{35\pi}{18}, 2\pi \right\} \textrm{ if } x \in [0, 2\pi ] \end{align*}$

    I'll leave it to you to pull out each individual solution
    Thanks from topsquark and jacks
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Compute Trig Function Values, Solve Trig Equation
    Posted in the Trigonometry Forum
    Replies: 1
    Last Post: September 8th 2011, 07:00 PM
  2. Trig word problem - solving a trig equation.
    Posted in the Trigonometry Forum
    Replies: 6
    Last Post: March 14th 2011, 07:07 AM
  3. Trig Equation with varied trig functions
    Posted in the Trigonometry Forum
    Replies: 12
    Last Post: April 12th 2010, 10:31 AM
  4. Replies: 1
    Last Post: July 24th 2009, 03:56 AM
  5. Replies: 1
    Last Post: July 24th 2009, 02:29 AM

Search Tags


/mathhelpforum @mathhelpforum